Activation of SGK1.1 Upregulates the M-current in the Presence of Epilepsy Mutations - Martin-Batista, Elva; Manville, Rían W.; Rivero-Pérez, Belinda; Bartolomé-Martín, David; Alvarez de la Rosa, Diego; Abbott, Geoffrey W.; Giraldez, Teresa (Frontiers in Molecular Neuroscience, 2021)
In the central nervous system, the M-current plays a critical role in regulating subthreshold electrical excitability of neurons, determining their firing properties and responsiveness to synaptic input. The M-channel is mainly formed by subunits Kv7.2 and Kv7.3 that co-assemble to form a heterotetrametric channel. Mutations in Kv7.2 and Kv7.3 are associated with hyperexcitability phenotypes including benign familial neonatal epilepsy (BFNE) and neonatal epileptic encephalopathy (NEE). SGK1.1, the neuronal isoform of the serum and glucocorticoids-regulated kinase 1 (SGK1), increases M-current density in neurons, leading to reduced excitability and protection against seizures. Herein, using two-electrode voltage clamp on Xenopus laevis oocytes, we demonstrate that SGK1.1 selectively activates heteromeric Kv7 subunit combinations underlying the M-current. Importantly, activated SGK1.1 is able to up-regulate M-channel activity in the presence of two different epilepsy mutations found in Kv7.2 subunit, R207W and A306T. In addition, proximity ligation assays in the N2a cell line allowed us to address the effect of these mutations on Kv7-SGK1.1-Nedd4 molecular associations, a proposed pathway underlying M-channel up-regulation by SGK1.1